3. PINK TIDE: GELOMBANG KEMENANGAN PRESIDEN KIRI PADA PEMILIHAN UMUM DI AMERIKA LATIN - Marten, Marten (FORUM, 2014)
Latin America history was very surprising. By the end of 21 century, no one has suspected that Latin America bear a movement at some states in this area, pink tide believed by the follower as the delivering birth of Socialism of 21 century. Sosialism Movement in Latin America assumed the including of phenomenal after super pounding of Liberation Theology that was expanding since early 1970. Previously, the socialism movement caused unbelievable in the middle of descend popularity socialism globally process after communism avalanche in Uni Soviet early 1990. Pink Tide started to be formed when most general elections conducted democratically in this area, which was won by leaders who have leftist-ideology such as Lula da Silva in Brazil ( 2002 and 2006). Nestor Kirchner in Argentina (2003), Evo Morales in Bolivia (2005); Daniel Ortega in Nicaragua (2006), Rafael Correa in Ekuador (2006) and Hugo Chavez in Venezuela (2006). This Phenomenon becomes more interesting because the strength of left group in Latin America declare their resistance in economy of neoliberal policies.